2022
DOI: 10.1200/edbk_351411
|View full text |Cite
|
Sign up to set email alerts
|

The Multimodal Management of Locally Advanced Rectal Cancer: Making Sense of the New Data

Abstract: In the past 40 years, the treatment of locally advanced rectal cancer has evolved with the addition of radiotherapy or chemoradiotherapy and providing (neo)adjuvant systemic chemotherapy to major surgery. However, recent trends have focused on improving our ability to risk-stratify patients and tailoring treatment to achieve the best oncologic outcome while limiting the impact on long-term quality of life. Therefore, there has been increasing interest in pursuing a watch-and-wait approach to achieve organ pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 110 publications
0
20
0
1
Order By: Relevance
“…Extramural venous invasion (EMVI) is tumor extension into veins beyond the muscularis propria and has been associated with poor prognosis. This finding on MRI is associated with local and distant recurrence 1–9 15 …”
Section: Mri Stagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Extramural venous invasion (EMVI) is tumor extension into veins beyond the muscularis propria and has been associated with poor prognosis. This finding on MRI is associated with local and distant recurrence 1–9 15 …”
Section: Mri Stagingmentioning
confidence: 99%
“…This finding on MRI is associated with local and distant recurrence. [1][2][3][4][5][6][7][8][9] One study showed 85% agreement between MRIdetected EMVI and that determined by surgical pathology. 15 Nodal disease is differentiated by locoregional node (localized disease) and nonlocoregional node (metastatic disease) involvement.…”
Section: Mri Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various forms and courses of radiotherapy have been employed to treat rectal cancer for over 50 years, characterizing the optimal total dose, treatment course, and subsequent timing to oncological proctectomy remains contentious 7,13 . Moreover, recently popularized “total” neoadjuvant chemoradiotherapy (TNT) and nonoperative “watch and wait” (W&W) protocols add more variables to a complex and partially defined equation and often add substantial time to the interval between completing radiotherapy and surgical resection 5,14–17 …”
Section: Introductionmentioning
confidence: 99%
“…7,13 Moreover, recently popularized "total" neoadjuvant chemoradiotherapy (TNT) and nonoperative "watch and wait" (W&W) protocols add more variables to a complex and partially defined equation and often add substantial time to the interval between completing radiotherapy and surgical resection. 5,[14][15][16][17] Altering the radiation-surgery interval (RSI) offers a series of hypothetical trade-offs for patients requiring proctectomy following radiation. Since the tumoricidal effects of radiation increase over time from exposure, the rates of partial and complete tumor regression improve with longer RSI, which likely impart oncologic benefit.…”
Section: Introductionmentioning
confidence: 99%